Factors influencing online shopping behaviour of youth customers in Malaysia after covid-19 pandemic - Nor Azma Rahlin; Ozzy Jas; Siti Nadhirah Mohamad Fauzi; Ayu Suriawaty @ Siti Aisyah Bahkia (Penerbit UNISZA, 2024)
Background and Purpose: The Movement Control Order (MCO) requires a higher demand for online services. In light of recent events in the business environment, it is becoming challenging to ignore online channels, including online shopping platforms. The current study investigates the impact of customer satisfaction, convenience, social media influence, and website on online shopping behaviour. Methodology: Two hundred respondents were selected based on the convenience sample. Online questionnaires were distributed to young Kota Kinabalu, Sabah, Malaysia customers. This case study was conducted after the Covid-19 pandemic in Kota Kinabalu, Sabah. Harman's Single Factor Test, Validity test, and Partial Least Square Structural Equation Model were used to validate the model of this study and the relationship between constructs. Findings: The results reveal that customer satisfaction, convenience, and social media influence are significantly related to the online shopping behaviour of youth in Malaysia after Covid-19 pandemic. Furthermore, the relationship between customer satisfaction and online shopping behaviour is higher than that between other factors in this study model. Contributions: In theory, this study contributes to understanding Malaysian youth customers' online shopping behaviour. Businesses must take full advantage of e-commerce platforms to ensure customer satisfaction and build customer trust through online shopping services.